Experience of academic staff in mentoring programs - Ireneusz Żuchowski; Nunzio Casalino; Bartosz Murat (International Journal of Management and Economics, 2022)
Mentoring programs developed at universities are an effective method of supporting student development. The participation in these programs brings them many benefits. These benefits include increased prestige in the community, gaining new experiences and achieving defined goals in the case of universities. It is essential to improve the mentoring programs implemented at universities. This article presents the results of research carried out within the framework of the BEGIN project implemented and funded under the Erasmusplus program. The aim of the research was to identify academic staff's experiences of participating in formal and informal mentoring programs. Ten in-depth interviews were conducted with respondents from Italy, Poland and Germany. A purposive selection method was used. The research provided clues with a practical dimension on how to implement mentoring programs, usefulness from the student's point of view, effectiveness and efficiency, and how to measure the impact of the program on students.
Keywords: J24; M53; I23; 650; academic teachers; Erasmusplus; mentoring; student development